Effect of Catholyte Concentration on Current Production During Chocolate Industry Wastewater Treatment by a Microbial Fuel Cell - Wulan, Diana Rahayuning; Notodarmojo, Suprihanto (Makara Journal of Technology, 2020)
Microbial fuel cells (MFCs) use bacteria as a catalyst to oxidize organic and/or inorganic substrates and produce electric currents. Wastewater could function as an electron donor in the anode chamber and, thus, represents a very promising energy source. Catholytes, as electron acceptors, influence power production in MFCs by increasing the availability of electrons. The present research aims to determine the influence of catholyte concentration on current production in an aerobic two-chamber MFC. Aerobic treatment was carried out in the two-chamber MFC operated in an incubator at 37  1 °C with and without aeration in the cathode chamber. Wastewater from the chocolate industry was used as a substrate and oxidized by using a bacterial consortium isolated from the sludge wastewater itself. The catholytes used were 0.01, 0.05, 0.1, and 0.3 N NaCl. In the presence of NaCl, the chemical oxygen demand (COD) removal efficiency in the cathode chamber of the MFC was approximately 65%–83% without aeration and 76%–89% with aeration after 72 hours. The current density increased as the catholyte concentration increased to 0.05 N, after which the oxidation process shifted from the anode chamber to the cathode chamber. Addition of O2 to the cathode chamber influenced current production.